Off-diagonal helicity density matrix elements for vector mesons produced in polarized e+e- processes - Anselmino, M.; Bertini, M.; Caruso, F.; Murgia, F.; Quintairos, P. [UNESP] (Springer Nature, 1999)
Final-state qq̄ interactions give origin to nonzero values of the off-diagonal element ρ1,-1 of the helicity density matrix of vector mesons produced in e+e- annihilations, as has been confirmed by recent OPAL data on φ, D*, and K*. New predictions are given for ρ1,-1 of several mesons produced at large XE and small pT - i.e., collinear with the parent jet - in the annihilation of polarized e+ and e-; the results depend strongly on the elementary dynamics and allow further nontrivial tests of the standard model.